CFD-informed surrogate modeling for rapid prediction of coupled pavement–air thermal response - Hamidreza Alinejad; Junsuk Kang; Junmo Lee; Young Sun Kwon; Seunghun Baek; Jung-Min Lee; Sang Rae Kim (Building and Environment, 2026)

Longitudinal association of chronic periodontitis with all-cause dementia, Alzheimer disease, vascular dementia, and mild cognitive impairment: a distributed network analysis - Gyubeom Hwang; So Hee Lee; Sang-Won Han; YoungSoon Yang; Soyoung Lee; Yeshin Kim; Yerim Kim; Rae Woong Park (GeroScience, 2026)

First report of lily symptomless virus infecting scarlet geranium (Pelargonium inquinans) in Korea - Min-Jae Kim; Hyo-Jeong Lee; Sang-Yun Cho; Rae-Dong Jeong (Journal of Plant Pathology, 2026)

Modeling and optimization of a trickle-bed reactor with hydrogen quenching for cost-effective hydrotreated biodiesel production - Yonghyun Lee; Jaehun Choi; Hyoung-il Kim; Jungho Jae; Jung Rae Kim; Sang Hwan Son (Fuel, 2025)

Fundamental modeling of microbial electrosynthesis system using porous electrodes for CO2-to-acetate conversion - Minji Kim; Jiin Yoo; Minsoo Kim; Ji Hun Kim; Yonghyun Lee; Huiwon Lee; Hyoung-il Kim; Jungho Jae; Jung Rae Kim; Sang Hwan Son (Bioresource Technology, 2025)

Oxygen-enriched carbon quantum dots from coffee waste: Extremely active organic photocatalyst for sustainable solar-to-H2O2 conversion - Do-Yeon Lee; Zeeshan Haider; Siva Kumar Krishnan; Thamaraiselvi Kanagaraj; Sang Hwan Son; Jungho Jae; Jung Rae Kim; Paskalis Sahaya Murphin Kumar; Hyoung-il Kim (Chemosphere, 2024)

Interactions between the calanoid copepod Acartia hongi and the bloom-forming dinoflagellates Karenia bicuneiformis and K. selliformis - Jin Hee Ok; Hae Jin Jeong; Ji Hyun You; Sang Ah Park; Hee Chang Kang; Se Hee Eom; Moo Joon Lee; Jung-Rae Rho (Marine Biology, 2024)
Copepods are a major component of metazooplankton and important prey for fish and invertebrates such as crabs, shrimps, and flatworms. Certain bloom-forming dinoflagellates can kill copepods, but there is little research on the interactions between copepods and the bloom-forming dinoflagellates Karenia bicuneiformis and K. selliformis . In this study, the survival and ingestion rates of the calanoid copepod Acartia hongi feeding on K. bicuneiformis and K. selliformis were determined as a function of prey concentration. On day 2, the survival of A. hongi incubated with K. bicuneiformis was 90–100% at all the tested prey concentrations, while that with K. selliformis was 0–20% at ≥ 582 ng C mL −1 . Compared to other harmful dinoflagellates from the literature, K. bicuneiformis caused low mortality of Acartia ; however, K. selliformis caused almost the highest mortality at similar dinoflagellate concentrations. With increasing mean prey concentration, the ingestion rates of A. hongi feeding on K. bicuneiformis increased on day 1, but those on K. selliformis did not increase. Acartia hongi stopped feeding on K. bicuneiformis at mean prey concentrations of ≥ 341 ng C mL −1 and K. selliformis at all prey concentrations on day 2. At the prey concentration of 1000 ng C mL −1 , the ingestion rate of A. hongi feeding on K. bicuneiformis was moderate among the rates of Acartia spp. feeding on harmful dinoflagellates; however, that on K. selliformis was the lowest. These results indicate that K. bicuneiformis and K. selliformis differentially affect the survival and ingestion rates of A. hongi .

Facile and rapid fabrication of wearable biosensors via femtosecond laser-directed micro-patterning with large-sized reduced graphene oxide for physiological monitoring - Hae-In Moon; Sungil Kim; Jeong Eun Byun; Young Won Kim; Yeon Wook Jung; Seung Geun Jo; Yujin Shin; Yeoul Kang; Sang Jun Kim; Eun-Su Lee; Hyung-Jong Lee; Min-Cheol Oh; et al. (Chemical Engineering Journal, 2024)

Molecular Detection for Two Abalone Shell-boring Species Polydora haswelli and P. hoplura (Polychaeta, Spionidae) from Korea using 18S rDNA and cox1 Markers - Soon Jeong Lee; Mun-Gyeong Kwon; Sang-Rae Lee (Ocean Science Journal, 2020)

First report of cucumber mosaic virus infecting Ledebouriella seseloides in Korea - Na-Kyeong Kim; Hyo-Jeong Lee; Hwi-Won Jeong; Seon-Min Go; Nam-Yeon Kim; Tae Ho Ryu; Sang-Yun Cho; Mi-Ri Park; Rae-Dong Jeong (Journal of Plant Pathology, 2020)

Peroxiredoxin 4 inhibits insulin-induced adipogenesis through regulation of ER stress in 3T3-L1 cells - Jae Yeop Kim; Mi Hye Kim; Hong Jun Lee; Jae-Won Huh; Sang-Rae Lee; Hyun-Shik Lee; Dong-Seok Lee (Molecular and Cellular Biochemistry, 2020)

Benthic Respiration and Nutrient Release Associated with Net Cage Fish and Longline Oyster Aquaculture in the Geoje-Tongyeong Coastal Waters in Korea - Sung-Han Kim; Hyung Chul Kim; Sang-Hwa Choi; Won-Chan Lee; Rae-Hong Jung; Jung-Ho Hyun; Suk Hyun Kim; Jae Seong Lee (Estuaries and Coasts, 2020)

Dieckol or phlorofucofuroeckol extracted from Ecklonia cava suppresses lipopolysaccharide-mediated human breast cancer cell migration and invasion - Young-Ju Lee; Jung-Hwan Park; Sang-Ah Park; Na-Rae Joo; Bong Ho Lee; Kyung Bok Lee; Sang-Muk Oh (Journal of Applied Phycology, 2020)

The First Molecular Evidence of Korean Zalophus japonicus (Otariidae: Sea Lions) from the Archaeological Site of Dokdo Island, Korea - Sang-Rae Lee; Yun-Bae Kim; Tongsup Lee (Ocean Science Journal, 2019)

Full Thickness Skin Expansion ex vivo in a Newly Developed Reactor and Evaluation of Auto-Grafting Efficiency of the Expanded Skin Using Yucatan Pig Model - Man-Il Huh; Soo-Jin Yi; Kyung-Pil Lee; Hong Kyun Kim; Sang-Hyun An; Dan-Bi Kim; Rae-Hyung Ryu; Jun-Sik Kim; Jeong Ok Lim (Tissue Engineering and Regenerative Medicine, 2018)

Perfluorooctane sulfonate exacerbates mast cell-mediated allergic inflammation by the release of histamine - Jun-Kyoung Lee; Soyoung Lee; Young-Ae Choi; Meiling Jin; Yeon-Yong Kim; Byeong-Cheol Kang; Min-Jong Kim; Hima Dhakal; Sang-Rae Lee; Sun-Uk Kim; Dongwoo Khang; Sang-Hyun Kim (Molecular & Cellular Toxicology, 2018)

Intraspecific variation of gene structure in the mitochondrial large subunit ribosomal RNA and cytochrome c oxidase subunit 1 of Pyropia yezoensis (Bangiales, Rhodophyta) - Il Ki Hwang; Seung-Oh Kim; Mi Sook Hwang; Eun-Jeong Park; Dong-Soo Ha; Sang-Rae Lee (Algae, 2018)

Eukaryotic Plankton Species Diversity in the Western Channel of the Korea Strait using 18S rDNA Sequences and its Implications for Water Masses - Sang-Rae Lee; Eun Hye Song; Tongsup Lee (Ocean Science Journal, 2018)

Wart-like spot formation on the fronds of Chondrus ocellatus (Gigartinales) by a brown alga, Mikrosyphar zosterae (Ectocarpales) in Korea - Cyr Abel Maranguy Ogandaga; Yeon Ju Na; Sang-Rae Lee; Young Sik Kim; Han Gil Choi; Ki Wan Nam (Journal of Applied Phycology, 2017)

Infection and cox2 sequence of Pythium chondricola (Oomycetes) causing red rot disease in Pyropia yezoensis (Rhodophyta) in Korea - Soon Jeong Lee; Bo Young Jee; Maeng-Hyun Son; Sang-Rae Lee (Algae, 2017)

Cloning and analysis of promoter region of mouse immunoglobulin germline γ3 transcripts - Beom-Seok Seo; Hee-Kyung Yoon; JongDae Shin; Ha-Yan Park; Sang-Hoon Lee; Ju-Eon Lee; Yung-Choon Yoo; Junglim Lee; Pyeung-Hyeun Kim; Seok-Rae Park (Genes & Genomics, 2016)

Mitochondria-targeted DsRed2 protein expression during the early stage of bovine somatic cell nuclear transfer embryo development - Hyo-Jin Park; Sung-Hun Min; Hoonsung Choi; Junghyung Park; Sun-Uk Kim; Seunghoon Lee; Sang-Rae Lee; Il-Keun Kong; Kyu-Tae Chang; Deog-Bon Koo; Dong-Seok Lee (In Vitro Cellular & Developmental Biology - Animal, 2016)

Some Elements in Thyroid Tissue are Associated with More Advanced Stage of Thyroid Cancer in Korean Women - Hye-Kyung Chung; Ji Sun Nam; Chul Woo Ahn; Yong Sang Lee; Kyung Rae Kim (Biological Trace Element Research, 2016)

The role of biochar, natural iron oxides, and nanomaterials as soil amendments for immobilizing metals in shooting range soil - Anushka Upamali Rajapaksha; Mahtab Ahmad; Meththika Vithanage; Kwon-Rae Kim; Jun Young Chang; Sang Soo Lee; Yong Sik Ok (Environmental Geochemistry and Health, 2015)

Molecular identification of the algal pathogen Pythium chondricola (Oomycetes) from Pyropia yezoensis (Rhodophyta) using ITS and cox1 markers - Soon Jeong Lee; Mi Sook Hwang; Myoung Ae Park; Jae Min Baek; Dong-Soo Ha; Jee Eun Lee; Sang-Rae Lee (Algae, 2015)

A nationwide survey and genetic analysis of rice stripe virus in South Korea during 2012–2013 - Sang-Yun Cho; Rae-Dong Jeong; Young-Nam Yoon; Dong Bum Shin; Hang-Won Kang; Bong Choon Lee (Journal of General Plant Pathology, 2015)

Ectopic expression of NtEF1 and NtEF2 promotes flowering and alters floral organ identity in Nicotiana tabacum - Ji Min Shin; Sang-Gyu Seo; Ji-Seong Kim; Haerim Jang; Mi-Rae Shin; Chanhui Lee; Sun-Hyung Kim (Plant Biotechnology Reports, 2015)

Ticks collected from migratory birds, including a new record of Haemaphysalis formosensis, on Jeju Island, Korea - Chang-Yong Choi; Chang-Wan Kang; Eun-Mi Kim; Sang Lee; Kyoung-Ha Moon; Mi-Rae Oh; Takeo Yamauchi; Young-Min Yun (Experimental and Applied Acarology, 2014)

Complete mitochondrial genome sequence of Pyropia yezoensis (Bangiales, Rhodophyta) from Korea - Mi Sook Hwang; Seung-Oh Kim; Dong-Soo Ha; Jee Eun Lee; Sang-Rae Lee (Plant Biotechnology Reports, 2014)

Inclusion compound formulation of hirsutenone with beta-cyclodextrin - Byeong Kil Ahn; Sang Gon Lee; Sung Rae Kim; Dong Hoon Lee; Myung Hwan Oh; Min Won Lee; Young Wook Choi (Journal of Pharmaceutical Investigation, 2013)

Complete sequence and genetic features of the mitochondrial genome of Pyropia tenera (Rhodophyta) - Mi Sook Hwang; Seung-Oh Kim; Dong-Soo Ha; Jee Eun Lee; Sang-Rae Lee (Plant Biotechnology Reports, 2013)

Topical formulation of retinyl retinoate employing nanostructured lipid carriers - Sang Gon Lee; Jae Han Jeong; Sung Rae Kim; Kyung Min Lee; Byeong Kil Ahn; Mean Hyung Kang; Young Wook Choi (Journal of Pharmaceutical Investigation, 2012)

Metagenomic examination of diversity within eukaryotic plankton from the ulleung basin in the East Sea of Korea - Sang-Rae Lee; TaeKeun Rho; Jung Hyun Oak; Jin Ae Lee; Tongsup Lee; Ik Kyo Chung (Journal of Plant Biology, 2012)

Cadmium resistance in tobacco plants expressing the MuSI gene - Young-Nam Kim; Ji-Seoung Kim; Sang-Gyu Seo; Youngwoo Lee; Seung-Woo Baek; Il-Sup Kim; Ho-Sung Yoon; Kwon-Rae Kim; Sun-Hyung Kim; Kye-Hoon Kim (Plant Biotechnology Reports, 2011)

Alteration of floral organ identity by over-expression of IbMADS3-1 in tobacco - Mi-Rae Shin; Sang-Gyu Seo; Ji-Seoung Kim; Seo-Bum Joen; Seung-Won Kang; Gung-Pyo Lee; Suk-Yoon Kwon; Sun-Hyung Kim (Transgenic Research, 2011)

Monitoring of selected veterinary antibiotics in environmental compartments near a composting facility in Gangwon Province, Korea - Yong Sik Ok; Sung-Chul Kim; Kwon-Rae Kim; Sang Soo Lee; Deok Hyun Moon; Kyoung Jae Lim; Jwa-Kyung Sung; Seung-Oh Hur; Jae E. Yang (Environmental Monitoring and Assessment, 2011)

Effective molecular examination of eukaryotic plankton species diversity in environmental seawater using environmental PCR, PCR-RFLP, and sequencing - Sang-Rae Lee; Jung Hyun Oak; Ik Kyo Chung; Jin Ae Lee (Journal of Applied Phycology, 2010)

Touch-induced gene (IbTCH1) from sweet potato [Ipomoea batatas (L.) Lam.]: molecular cloning and functional analysis - Sang-Gyu Seo; Ji-Seong Kim; Seung-Won Kang; Mi-Rae Shin; You-Sun Yang; Gung-Pyo Lee; Jin-Sung Hong; Sun-Hyung Kim (Plant Biotechnology Reports, 2008)

A Cuticle Protein Gene from the Japanese Oak Silkmoth, Antheraea yamamai: Gene Structure and mRNA Expression - Bo Yeon Kim; Nam Sook Park; Byung Rae Jin; Bong Hee Lee; Su Il Seong; Jae Sam Hwang; Jong Su Chang; Sang Mong Lee (Biotechnology Letters, 2005)

Mitochondrial DNA Sequence-Based Population Genetic Structure of the Firefly, Pyrocoelia rufa (Coleoptera: Lampyridae) - Sang-Chul Lee; Jin-Sik Bae; Iksoo Kim; Hirobumi Suzuki; Seong-Ryul Kim; Jong-Gill Kim; Keun-Young Kim; Won-Jin Yang; Sang-Mong Lee; Hung-Dae Sohn; Byung-Rae Jin (Biochemical Genetics, 2003)

Cloning of the fibroin gene from the oak silkworm, Antheraea yamamai and its complete sequence - Jae-Sam Hwang; Jin-Sung Lee; Tae-Won Goo; Eun-Young Yun; Kwang-Sik Lee; Yong-Sung Kim; Byung-Rae Jin; Sang-Mong Lee; Keun-Young Kim; Seok-Woo Kang; Dong-Sang Suh (Biotechnology Letters, 2001)